Conferindo legitimidade: a participação democrática no controle concentrado de constitucionalidade no STF - Amaral, Larissa Maciel do (2014)
The judicial function in modern democracy it´s not the same than after. Modern democracy evolves a participatory democracy, which besides protecting citizens rights to liberty, equality and solidarity, denotes a more intense participation of citizens and that goes beyond participation through voting. The Legitimacy can not be mean iqual votes, simply. Having two of the Powers constituted, elected, and disbelief in representation by citizens, I´s not correct who that the elective model would be an exit to the legitimacy of the judiciary. Democratics Inflows and pluralism must also be present in the judiciary, especially in Judicial Cases of Concentrate Control of Constitution, which contains true normative purposes. The procedural plurality, combined with a good foundation will be ensure legitimacy to the judiciary in modern democracies.